Sylvia melanocephala Sardinian Warbler - Herrando, Sergi (2021)
The EBBA2 project was carried out by the EBCC network of partner organisations from 48 countries. In total, around 120,000 fieldworkers contributed data to the atlas, the great majority of them on a voluntary basis. As such this project constitutes one of the biggest citizen science projects on biodiversity ever. Data collection and analysis followed a rigorous scientific protocol, led by a team of researchers from ornithological institutes with many years of experience in atlas work. The huge fieldwork effort resulted in unprecedented geographical coverage for a biodiversity atlas in Europe, including all areas up to the Ural Mountains and the Caspian Sea that were not well covered for EBBA1. These data were mainly collected for the period lasting from 2013 to 2017.